The Aleut language : the elements of Aleut grammar with a dictionary in two parts containing basic vocabularies of Aleut and English - Geoghegan, Richard Henry, 1866-1943; Martin, Fredericka I ([Washington, D.C.] : United States Dept. of the Interior, 1955)
Mode of access: Internet.